The Relationship between Body Mass Index (BMI), Sleep Quality, and Fertility Quality of Life among Infertile Couples - Zahari, Zaidamerrayati; Sham, Fatimah; Mohd Fahmi Teng, Nur Islami; Arshad, Akmal Hisyam; Yatim, Rasidah (The Malaysian Journal of Nursing (MJN), 2025)
Background: Infertility can profoundly impact various aspects of a couple’s life, including their body mass index (BMI), sleep quality, and overall quality of life. This cross-sectional study aimed to explore the relationship between BMI, sleep quality, and quality of life among infertile couples. Methods: Conducted at a tertiary hospital in Selangor, the study involved 126 participants (63 couples). BMI, sleep quality (measured using the Pittsburgh Sleep Quality Index, PSQI), and quality of life (measured using the Fertility Quality of Life, FertiQoL) were assessed. Data were analysed using IBM SPSS version 29. Results: Poor sleep quality (PSQI score >5) was observed in 10.3% of participants, while 89.7% had good sleep quality (PSQI score <5). The mean BMI was 27.52 ± 6.48. This study revealed no significant relationship between all three variables (body mass index, sleep quality, and quality of life) among the infertile couple as the p-value was more than 0.05. Conclusion: These findings suggest that while BMI does not significantly impact the quality of life among infertile couples, sleep quality may have a minor influence; by addressing sleep quality issues and understanding their relationship with BMI and overall health, nurses can contribute to improving the quality of life for patients, particularly those struggling with infertility and related concerns.